POLA PENGELUARAN MAKANAN DAN NON MAKANAN PADA KELUARGA PRA-SEJAHTERA DAN SEJAHTERA 1 DI KECAMATAN FATULEU KABUPATEN KUPANG - Budi, Maria; Nendissa, Doppy Roy; Hendrik, Ernantje (Buletin Ilmiah Impas, 2023)
This study aims to determine the Expenditures and differences in the Pattern of Food and Non-Food Expenditures in Pre-Prosperous and Prosperous 1 Families in Fatuleu District, Kupang Regency. To find out food and non-food consumption expenditures, descriptive methods were used, while to find out differences in food and non-food expenditure patterns in Pre-Prosperous and Prosperous 1 Families, data analysis techniques were carried out using Chi Square Two Independent Samples. The results of the study show that (1) the average spending on food and non-food consumption in pre-prosperous families: food expenditure is Rp. 759,000 and non-food expenditure amounted to Rp. 587,000. While the average for food and non-food expenditure in the Prosperous Family 1: food expenditure amounts to Rp. 1,178,920 and non-food expenditure amounted to Rp. 898,480. Thus the Pre-Prosperous and Prosperous 1 families prioritize spending on food compared to non-food. (2) There is a difference in the pattern of food expenditure for Pre-Prosperous and Prosperous 1 families with a food value of 1,000 and a non-food value of 0.728. Thus there are significant differences in the pattern of food and non-food expenditure in Pre-Prosperous and Prosperous 1 families. The existence of significant differences in the pattern of food and non-food expenditure in Pre-Prosperous and Prosperous 1 families shows that people prioritize spending on food consumption compared to non-food consumption